Echopraxia Speech Disorder in Elementary School Teacher Education Students: A Psycholinguistic Approach - Ezik Firman Syah; Irma Damayantie; Irma Savitri Sadikin; Andri Purwanto (Proceeding of the International Conference on Global Education and Learning, 2024)
This latah trend phenomenon is inseparable from the development of the television entertainment world in comedy shows in Indonesia, which considers the disorder of latah speech to be something funny among the younger generation. So, students consider someone who is latah in class to be something that is considered funny. This study aimed to identify the echopraxia latah speech disorder in elementary school teacher education students with a psycholinguistic approach. This research method uses the Milles and Huberman model content analysis method with data collection techniques conducting observations, interviews, and documentation on students of the Elementary School Teacher Education Study Program at Esa Unggul University. The study results from three students who experienced echopraxia latah disorders. The sounds produced were categorized as moderate and caused noise during the learning process in class. This is because the noise created in the classroom is not from the latah utterances issued but because of the response of the classroom environment, which makes it noisy because someone who experiences echopraxia latah disorders does not only repeat their words but is followed by latah movements that are spoken. The causes of echopraxia latah disorders include spontaneity, daydreaming, being surprised when talking and being surprised from behind.